(untitled) (Third Sector Social Economic Review, 2023)
Epidemics, which affect the whole world and are called pandemics, have psychological, social, political and economic effects as well as medical effects for humanity from past to present. It is possible to evaluate the Covid 19 pandemic, which emerged in China in 2019, spread rapidly all over the world and shook societies deeply, as a disaster. With the restrictions applied to prevent the disease, economic, psychological and social changes have occurred in every part of the society. It is inevitable that the multidimensional and important consequences of the Covid 19 Pandemic will not have an impact on rural life. In this study, it is aimed to understand the extent of the effects of the Covid 19 Pandemic in rural life. In the research, it was tried to reach how the Covid 19 pandemic affected rural life, as a result of the findings obtained through in-depth interviews with sixty-four participants from four villages of Sakarya, where different agricultural activities were carried out. The data obtained as a result of the research were analyzed with the Nvivo qualitative data analysis program. In the results of the research, the increasing economic difficulties with the pandemic draw attention as the important effect of the pandemic in rural life. Since no restrictions are applied in the realization of agricultural activities, while there is no problem in production, it is seen that there is a problem in sales. The realization of agricultural activities in rural life as foreign-dependent, the seed to be used in production, medicine, fertilizer, diesel; The importation of feed in animal husbandry causes agricultural activities, which are the main economic activity of the rural areas and provide nutrition to the society, to be made expensive. Expensiveness is also increasing with the pandemic, which shows that it negatively affects the income of the rural people. The pandemic reveals the necessity of having a self-sufficient potential in terms of safe agricultural practices and the product obtained in agricultural activities all over the world and makes it necessary to make arrangements in this direction.